2019
DOI: 10.1097/rti.0000000000000379
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Early Lung Cancer, Chronic Obstructive Pulmonary Disease, and Cardiovascular Disease (the Big-3) Using Low-dose Chest Computed Tomography

Abstract: Lung cancer, chronic obstructive pulmonary disease, and cardiovascular disease are highly prevalent in the general population and expected to cause most deaths by 2050. For these "Big-3," treatment might cure, delay, or stop the progression of disease at a very early stage. Lung nodule growth rate (a biomarker for lung cancer), emphysema/air trapping (a biomarker for chronic obstructive pulmonary disease), and coronary artery calcification (a biomarker for cardiovascular disease) are imaging biomarkers of earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 99 publications
1
45
0
Order By: Relevance
“…Namely, volume-based management for lung nodules is associated with a far lower rate of unnecessary referral as compared to diameter-based management, with a comparable lung cancer detection rate in a European population 18 . Besides, a review indicated that screening for COPD and CVD, in addition to lung cancer, may significantly increase the benefits of low-dose CT lung cancer screening 19 . Given the large disease burden caused by the Big-3 in China, a developing country with limited medical resources 20 , introducing quantitative CT screening for Big-3 diseases could have a positive impact on the Chinese healthcare and society by reducing the rate of unnecessary referrals for further investigation in terms of lung nodules detection and increasing screening benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, volume-based management for lung nodules is associated with a far lower rate of unnecessary referral as compared to diameter-based management, with a comparable lung cancer detection rate in a European population 18 . Besides, a review indicated that screening for COPD and CVD, in addition to lung cancer, may significantly increase the benefits of low-dose CT lung cancer screening 19 . Given the large disease burden caused by the Big-3 in China, a developing country with limited medical resources 20 , introducing quantitative CT screening for Big-3 diseases could have a positive impact on the Chinese healthcare and society by reducing the rate of unnecessary referrals for further investigation in terms of lung nodules detection and increasing screening benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Developed countries are able to spend more money on screening tools such as computed tomography (CT), perform more kinds of advanced surgeries involving, for example, videoassisted techniques, and provide more precise therapies such as image-guided radiotherapy (IGRT) and immunotherapy. 7,12,13 All these therapies show benefits on survival. 7 The incidence and mortality rates for lung cancer are relatively high in developed countries such as North America.…”
Section: Discussionmentioning
confidence: 99%
“…Could implementation of lung cancer screening implementation be hindered due to concerns with the complex management of two other leading causes of death (CAD and COPD) in this heavily tobacco-exposed cohort? Fortunately, this appears unlikely as integrating care for the three leading causes of tobacco-related chronic disease is already happening at leading screening centers [38]. A more inclusive approach with thoracic CT imaging in tobacco-exposed cohorts will be disseminated through existing support for lung cancer screening, which is already federally reimbursed.…”
Section: Moving Forwardmentioning
confidence: 99%
“…In this fashion, routinely acquiring additional information about the two other leading causes of premature death (COPD and heart disease) can be done at an incremental cost within the screening effort. Leading screening programs already have considerable experience in performing this multi-disease screening, with clinicians already integrating this complex imaging information into productive discussions with individuals undergoing such screening [38].…”
Section: Moving Forwardmentioning
confidence: 99%